Positive Influences of Integrating Information Communication Technology in Teaching English at a Technical and Vocational Training College - Mogashoa, Tebogo; Makaring, Busisiwe (Journal of Ecohumanism, 2024)
The paper investigated the positive influence of integrating Information Communication Technology (ICT) in teaching English to National Certificate NC (V) students at a Technical and Vocational Education and Training (TVET) college. A qualitative research approach was used in this research to explore and determine ways in which ICT can be used in teaching English. The research’s participants were fifteen NC (V) lecturers offering English. Semi-structured interviews and focus group interviews were conducted with Heads of Departments (HODs), Senior Education Specialists (SES), Education Specialists (ES), and NC(V) English lecturers. This paper found that there are barriers when it comes to integrating ICT in teaching English, and these were teacher-level barriers, student-level barriers, and school-level barriers. It is hoped that this research will contribute towards strategic ways that will ensure that ICT is integrated in teaching English at Nkangala TVET College, as this will improve students’ class attendance and enhance teaching and learning.